FOUR PILLARS OF THE STORY - Komiljon Hamrayev Olmasovich (Scholar Express Journal, 2023)
The article analyzes the stories of Khalmuhammad Karimi. The artistry and subject scope of the writer's stories in the collection "Samarkand season" published in Turkey were studied. The article focuses on 4 aspects of the writer's stories. In this case, the time of occurrence of the story event is built on the basis of a specific poetic situation or a single sentence, a metamorphosing feature and a means of artistic contrast
Keywords: narrative art; artistic chronotope; sentence